Expanding the potential of standard flow cytometry by extracting fluorescence lifetimes from cytometric pulse shifts. Issue 12 (1st October 2014) - Cao, Ruofan; Naivar, Mark A.; Wilder, Mark; Houston, Jessica P.
Abstract Fluorescence lifetime measurements provide information about the fluorescence relaxation, or intensity decay, of organic fluorophores, fluorescent proteins, and other inorganic molecules that fluoresce. The fluorescence lifetime is emerging in flow cytometry and is helpful in a variety of multiparametric, single cell measurements because it is not impacted by nonlinearity that can occur with fluorescence intensity measurements. Yet time‐resolved cytometry systems rely on major hardware modifications making the methodology difficult to reproduce. The motivation of this work is, by taking advantage of the dynamic nature of flow cytometry sample detection and applying digital signal processing methods, to measure fluorescence lifetimes using an unmodified flow cytometer. We collect a new lifetime‐dependent parameter, referred to herein as the fluorescence‐pulse‐delay (FPD), and prove it is a valid representation of the average fluorescence lifetime. To verify we generated cytometric pulses in simulation, with light emitting diode (LED) pulsation, and with true fluorescence measurements of cells and microspheres. Each pulse is digitized and used in algorithms to extract an average fluorescence lifetime inherent in the signal. A range of fluorescence lifetimes is measurable with this approach including standard organic fluorophore lifetimes (∼1 to 22 ns) as well as small, simulated shifts (0.1 ns) under standard conditions (reported herein). This contribution demonstrates how digital data acquisition and signal processing can reveal time‐dependent information foreshadowing the exploitation of full waveform analysis for quantification of similar photo‐physical events within single cells. © 2014 The Authors. Published by Wiley Periodicals, Inc.